Sistem Penjualan Petshop Menggunakan Algoritma Machine Learning Pada Galaxy Petshop Semarang - Cahyani, Bella Garin Dwi; Handoko, Widiyanto Tri (MEANS (Media Informasi Analisa dan Sistem), 2023)
A recommendation system is a system that can provide recommendations on a particular object that can be used to assist system users in making a decision. This study iams to implement a recommendation system using the collaborative filtering method in e-commerce for the pet shop selling system. With e-commerce, customers can make purchases on-line without having to come to the costs. With the recommendation system provided, customers will get recommendations for the product to be purchased as a consideration in determining product choices. The collaborative filtering method carries out the process of filtering or evaluating objects based on oter people’s opinions, by providing information to consumers, based on similar characteristics